The heir affair [compact disc, unabridged] - Cocks, Heather; Morgan, Jessica, 1975- (Cocks, Heather. Royal we., 2020)
After a scandalous secret turns their fairy-tale wedding into a nightmare, Rebecca "Bex" Porter and her husband Prince Nicholas are in self-imposed exile. The public is angry. The Queen is even angrier. And the press is salivating. Cutting themselves off from friends and family, and escaping the world's judgmental eyes, feels like the best way to protect their fragile, all-consuming romance. But when a crisis forces the new Duke and Duchess back to London, the Band-Aid they'd placed over their problems starts to peel at the edges.